The factors affecting the auditor selection decisions of FTSE 350 companies in competitive tenders - Drew, Philip (Cranfield University, 2015)
Auditing provides an important role supporting the function of financial markets where information asymmetry exists between shareholders and management. The audit market for the largest publicly listed UK companies, those within the FTSE 350, has however come under scrutiny following a number of financial scandals and, driven both by quality and competition concerns as the largest audit firms, the “Big 4” are dominant. Auditor tenure and long periods without competitive tenders have been recurrent concerns and yet how companies select their auditors is under researched. This study examines the influences on the complex decision process underlying auditor selection in FTSE 350 companies during an important period, namely that between the acquisition of Arthur Andersen by Deloitte in August 2002 and the introduction of the September 2012 UK Corporate Governance Code by the Financial Reporting Council. Based on a social constructionist philosophical perspective and adopting a grounded approach, the study covers 60 auditor selection decisions (over half of those identified in the research period) and includes in depth interviews over a period of two years with those who had recently been involved in a FTSE 350 auditor selection process; both from the buy-side and the sales-side. A conceptual model is developed which illustrates five factor groups that this research identified as influencing auditor selection in typically comprehensive proposal processes. These were: Relationships at the start of the proposal process, Service design, Capabilities and competences of the bidding firms, Behavioural influences during the proposal process and Final decision making. It also identifies interrelationships between these factor groups. These results are important because they inform theory and practice at a time when auditor change is becoming a statutory requirement. The study also has implications for other complex purchases of intangible services, particularly other professional services, and potentially for complex decision situations more generally.